Reference genes for livestock gene expression profiling – Literature review - Simon, Ádám; Zakarné Aszalós, Zsuzsa; Jávor, András; Czeglédi, Levente (Acta Agraria Debreceniensis, 2017)
Quantitative real-time polymerase chain reaction (qPCR) is an essential tool for understanding animal cell’s response to developmental progression or to different experimental conditions at gene expression level. However the reliability of this method heavily lies on proper normalization (measuring a target and a reference gene’s expression from the same sample to correct for technical related variations). Our literature review aimed to summarize the articles addressing the most important livestock species in regards of reference gene stability used as normalizers for quantitative real-time polymerase chain reaction experiments. Stably expressing reference genes were categorized into 14 distinct groups according to gene function. The number of reference genes tested and the publication numbers according to years and the ranking algorithms were also noted. Counting showed that genes encoding ribosomal protein components are ranked as most stable in majority of cases and therefore should be taking into account for qPCR stable normalizer gene finding experiments.